Analisis Peran Dan Kualitas Konsultan Pajak Terhadap Kepatuhan Wajib Pajak Pada Kantor Konsultan Pajak Ratna Tio - Fadila, Reihana; Simbolon, Ramadona; Barus, Muhammad Joni; Sonata, Ilham; MS, Abdul Rasyid; Elviani, Sri (Universitas Islam Islam Sumatera Utara, 2024)
The purpose of this study is to find out whether the role of tax consultants and the quality of consultants have an influence on taxpayer compliance at the Ratna Tio Tax Consultant Office. This study uses a quantitative method with an observational analytical study design and cross-sectional thinking. The sample size for this study is 100 taxpayers, 20 corporate taxpayers and 80 individual taxpayers. The type of sampling in this study is Non-Probability and the sample collection method used is Purposive Sampling. The data collection method in this study uses a questionnaire containing questions regarding the quality and role of tax consultants, as well as compliance with paying taxes. The study uses a multiple linear regression analysis test using SPSS 21. Based on the results of the analysis, the role of tax consultants partially has a significant effect on taxpayer compliance. P-Value (0.000 < 0.05). The quality of the Tax Consultant does not have a significant influence on Taxpayer Compliance. P-Value (0.785 > 0.05). From the results obtained, the researcher conveyed suggestions to the DJP to develop insight regarding taxpayers in the field of taxation, so that by developing insight regarding taxpayers, taxpayers will develop compliance in paying their taxes.